PERSEPSI PENDERITA TERHADAP PENGOBATAN DAN KESEMBUHAN PENYAKIT TUBERKULOSIS PARU DI KOTA PEKANBARU - Pernadi, Muhammad Octa; ", Suyanto; Simbolon, Rohani Lasmaria (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTTuberculosis ( TB ) is one of the world's health problems. Indonesia is one of the countries with high TB incidence. There are 450,000 TB cases and 64,000 deaths per year or about 169 deaths per day. The TB case detection rate ( CDR ) in Indonesia is still below the national target. Low case detection rate of TB in Indonesia is influenced by several factors, which one of that is the perception of the patient to the treatment and recovery of TB disease. This research is qualitative by using in-depth interviews and focus group discussions. By using the snowballing sampling technique obtained 12 samples from patients with pulmonary TB population and health care. The results obtained are the description of the informant's perception of TB disease is largely lacking. There are the informants who do not know the exact cause of TB. Perceptions of informants to the treatment of TB disease is almost the same, it can be seen from all over the informants believed that the treatment provided by the health service will grant a recovery of TB disease than traditional treatments. Perceptions of informants to the recovery of TB disease is almost the same too, it can be seen from the statement of the entire informants feel confident and believe in doing the treatment at the health center can cure TB disease .Key words: tuberculosis, perception, treatment, recovery